A Complete Review on : Liposomes (International Journal of Scientific Research in Science and Technology, 2024)
Liposomes are a drug delivery system that is adaptable and optimistic. The benefits of liposomes over other drug delivery systems include site-targeting, prolonged or controlled release, protection of drugs from degradation and clearance, higher therapeutic effects, and fewer toxic adverse effects. As effective drug carriers in pre-clinical and clinical studies, liposomes provide a wide range of benefits and uses. Additionally, issues pertaining to liposomal stabilization, efficient targeting techniques, and some of their drawbacks were discussed. Formulation of liposomes has enabled the modification of drug biodistribution of many drugs, hence improving the therapeutic properties of those compounds.